Artery of Percheron in the Differential Diagnosis of Acute Altered Mental Status - Maria Isabel Pérez Pañart; Beatriz Sierra Bergua (Case Reports in Medicine)
Bilateral thalamic infarction is a rare entity (it occurs in 0.6% of ischemic strokes) and can be confused with other vascular etiologies such as basilar syndrome and deep cerebral venous thrombosis, as well as neoplasms, infections, or toxins. It is typically characterized by the triad of altered mental status, vertical gaze paralysis, and memory impairment, although their symptoms can be highly variable. We describe the case of a young man who came to the emergency department presenting diplopia, speech alteration, and decreased level of consciousness with frequent fluctuations. Baseline computerized tomography was normal, and because of the clinical findings, thrombolysis was performed. Subsequently made magnetic resonance showed a bilateral acute thalamic infarction caused by an obstruction of the Percheron artery. Although Percheron syndrome has been previously described in medical journals, our case is an unusual case in which we could perform an acute intravenous thrombolytic treatment. Besides, it is important for emergency physicians to enclose the Percheron syndrome in the differential diagnosis of coma in young people so that emergent treatments such as thrombolysis can be employed.